Tâlib Divanı ve incelenmesi - Şahin, Banu Gezer (My University, 2009)
Bu çalışmaya konu olarak “Bosnalı Tâlib Dîvânı” seçilmiştir. Türkçe olarak kaleme alınmış bu eserin bulunan nüshası İstanbul’da Süleymaniye Ktp., Ali Emiri Efendi, nr. 256’da kayıtlı olup 31 varaktır. Çalışma dört bölümden oluşmaktadır. Birinci bölümde şairin hayatı ve edebî kişiliği ele alınmış, İkinci bölümde Dîvân biçim açısından, Üçüncü bölümde içerik özellikleri bakımından incelenmiştir. Dördüncü bölüm ise Dîvân’ının transkripsiyonlu metninden oluşmaktadır. Metnin, Arap harflerinden Lâtin harflerine aktarılmasında ilmî çevriyazı sistemine uyulmuştur.

As the topic of our study, we have chosen the work Dîvân which was written by Tâlib. The copy of this work written in Turkish is registered in “Ali Emirî Efendi” section with the number 256, in the Suleymaniye Library, in İstanbul and it contains 31 sheets. Our work includes four main parts: In the first part, we studied on the poet’s biography and his literary personality. In the second part, we examined the Divan as a form, In the third one, we studied on the content of the text. the fourth one contains a text with transcriptions of the work which is named “Tâlib Dîvânı”. When transliterating the text from Arabic letters to Latin ones, we adapted the system of scientific transliteration wrting.
Keywords: Divan Edebiyatı; Türk Dili